2018
DOI: 10.1038/s41598-018-27676-8
|View full text |Cite
|
Sign up to set email alerts
|

LSD1-ERRα complex requires NRF1 to positively regulate transcription and cell invasion

Abstract: Lysine-specific demethylase 1 (LSD1) exerts dual effects on histone H3, promoting transcriptional repression via Lys4 (H3K4) demethylation or transcriptional activation through Lys9 (H3K9) demethylation. These activities are often exerted at transcriptional start sites (TSSs) and depend on the type of enhancer-bound transcription factor (TFs) with which LSD1 interacts. In particular, the Estrogen-Receptor Related α (ERRα) TF interacts with LSD1 and switches its activities toward H3K9 demethylation, resulting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Such low overlap may point to significant differences between steady-state transcriptome and H3K27ac status reflecting differences between chromatin modifications associated with transcriptional activity of the locus and total RNA levels at the equilibrium between RNA synthesis and stability. Several studies propose LSD1 as a factor involved in regulation of promoter activities (Ferrari-Amorotti et al, 2013;Ambrosio et al, 2017;Carnesecchi et al, 2017;Zhang et al, 2018). To address how LSD1 occupancy of promoters is affected in the presence of HOTAIR, we performed CUT&RUN profiling of LSD1 in our system.…”
Section: High-migration Signature (Hms)mentioning
confidence: 99%
“…Such low overlap may point to significant differences between steady-state transcriptome and H3K27ac status reflecting differences between chromatin modifications associated with transcriptional activity of the locus and total RNA levels at the equilibrium between RNA synthesis and stability. Several studies propose LSD1 as a factor involved in regulation of promoter activities (Ferrari-Amorotti et al, 2013;Ambrosio et al, 2017;Carnesecchi et al, 2017;Zhang et al, 2018). To address how LSD1 occupancy of promoters is affected in the presence of HOTAIR, we performed CUT&RUN profiling of LSD1 in our system.…”
Section: High-migration Signature (Hms)mentioning
confidence: 99%
“…It has been suggested that NRF1 is essential for lysine-speci c demethylase 1 (LSD1) histone modi cation. The complex of NRF1, LSD1 and oestrogen-receptor related α (ERRα) is required for cell invasion in a matrix metalloprotease 1 (MMP1)dependent manner [34]. NRF1 also forms an activator complex with egl-9 family hypoxia inducible factor 2 (EglN2) to promote ferridoxin reductase (FDXR) transcription activation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that LSD1 can demethylate H3K4mel/2 and H3K9mel/2, thereby regulating downstream gene transcription. LSDl can remove methylation of the tumor suppressor protein p53 K370, inhibit p53 activity, and inhibit p53 target gene expression [11][12][13][14] .…”
Section: Discussionmentioning
confidence: 99%